Establishment of permissible limits for leaching substances from bone substitutes containing hydroxyapatite and beta-tricalcium phosphate - Chernobrovchenko Vadym; Dyadyura Kostiantyn; Balynskyi Mark (Lviv Politechnic Publishing House, 2021)
It has been proven that the main factor in the uncertainty of laboratory results is biological variation, that is, a change in the composition of human biomaterials, reflecting the course of life processes in the body and is characterized by a combination of the constancy of the internal environment and dynamic fluctuations around the homeostasis point. The paper offers objectively substantiated recommendations for the accuracy of laboratory tests, established maximum allowable values of analytical errors of quantitative research methods (measurements) of physical quantities (composition and properties of components of biological materials, analytes) in samples of biological materials. The interpretation of LOD and LOQ for detecting the concentration of leaching micro-impurities in the bioliquid. The identified patterns indicate that the elements of micro impurities have different dissolution rates. The ratio of hydroxyapatite/tricalcium phosphate affects the dissolution rate of the material: the higher the content of β-tricalcium phosphate, the higher the dissolution rate. The results of the research allow establishing recommendations for reducing inaccuracies in determining the composition of bone substitutes based on hydroxyapatite/β-tricalcium phosphate, which is associated with manifestations of biological variation, reflecting the body’s response to various environmental factors and subject to statistical laws. Key words: Standardization; Validation method; Limit of detection; Limit of quantification; Bone substitutes.